Bio-social correlates of indoor air pollution among women residing in rural areas of Mysuru - R., Yogendra D.; Kulkarni, Praveen; Basheer, Sayana; R., Pragadesh; Shabadi, Nayanabai (International Journal Of Community Medicine And Public Health, 2024)
Background: Indoor air pollution (IAP) remains a major global public health hazard more so in developing countries where the use of biomass fuels is still very common. Since women tend to be in charge of cooking and young children commonly spend time with their mothers while they are cooking, women and young children are disproportionately affected. In this background, the present study was proposed to assess the bio-social correlates of IAP among women residing in rural areas. Methods: A cross-sectional study was conducted in rural field practice areas of JSS Medical College, Mysuru for six months. Totally 210 households were included by probability proportionate to the size sampling technique. Data was collected by structured questionnaire with details on socio-demographic characteristics, house and fuel characteristics and indoor air pollution meter values of particulate matter (PM) 1, 2.5, 10 respectively. Results: Among 210 study participants, 28 (13%) had indoor air pollution in their houses. 99% of the households were using LPG. The mean concentrations of pollutants like PM10, PM2.5 and PM1.0 were higher among the houses with indoor air pollution compared to their counterparts (p<0.001). A statistically significant association was found between age, socioeconomic status, and poverty line and the presence of indoor air pollution. Conclusions: The present study showed that IAP had a strong relation to socio-cultural factors such as age, poverty and economic level. As women are involved in cooking in the majority of Indian households, they are more prone to be affected by the negative effects of solid fuel usage.